2022
DOI: 10.14202/vetworld.2022.2052-2058
|View full text |Cite
|
Sign up to set email alerts
|

The first study on the occurrence of bovine herpesviruses in the wild fauna of the Moscow region, Russia

Abstract: Background and Aim: Some pathogens that cause infections in cattle are found in wild artiodactyls. Their prevalence, possible impact on the population of free-living animals, and the spread of infectious pathology in livestock have yet to be studied. We investigated the occurrence of bovine herpesviruses (BoHV-1, BoHV-4, and BoHV-6) among wild moose and roe deer in 8 areas of the Moscow region in the Russian Federation. Materials and Methods: One hundred and one tissue samples and nasal swabs of 24 moose and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Eleven (3.75% buffaloes were found to carry BoAHV5 DNA; four (1.36%) animals contained BuAHV1 DNA; two (0.68%) contained BoAHV1 DNA, and one (0.34%) animal was co-infected with BoAHV1 and BoAHV5. Although other authors have reported BoAHV1 infections in sheep, goats, cervids, and buffaloes [39][40][41], this is the first report on BoAHV5 detection in water buffaloes, confirming the susceptibility of water buffaloes not only to BoAHV1 and BuAHV1, but also to BoAHV5 [19][20][21]. It is interesting to compare our results with those similar studies conducted in trigeminal ganglia of cattle from Brazil and Uruguay.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Eleven (3.75% buffaloes were found to carry BoAHV5 DNA; four (1.36%) animals contained BuAHV1 DNA; two (0.68%) contained BoAHV1 DNA, and one (0.34%) animal was co-infected with BoAHV1 and BoAHV5. Although other authors have reported BoAHV1 infections in sheep, goats, cervids, and buffaloes [39][40][41], this is the first report on BoAHV5 detection in water buffaloes, confirming the susceptibility of water buffaloes not only to BoAHV1 and BuAHV1, but also to BoAHV5 [19][20][21]. It is interesting to compare our results with those similar studies conducted in trigeminal ganglia of cattle from Brazil and Uruguay.…”
Section: Discussionsupporting
confidence: 83%
“…Unlike buffaloes and cattle, wild animals have not been domesticated, and the cohabitation between wildlife and current animal production systems has been limited. There are practically no data on the occurrence of BoAHV5 in wild animals [41]; therefore, we cannot make assumptions on that. What is apparent is that recombination events do occur between domesticated species.…”
Section: Discussionmentioning
confidence: 99%
“…The first subfamily contains five genera: Simplexvirus , Varicellovirus , Mardivirus , Iltovirus and Scutavirus [ 1 ]. The Varicellovirus genus of the family Herpesviridae includes nearly two hundred viruses isolated from various hosts [ 2 , 3 , 4 , 5 , 6 ]. The Varicellovirus genus includes a cluster of viruses antigenically and genetically related to bovine herpesvirus 1 (BoHV-1), such as bubaline herpesvirus 1 (BuHV-1), bovine herpesvirus 5 (BoHV-5), caprine herpesvirus 1 (CpHV-1), cervid herpesviruses 1 (CvHV-1) and 2 (CvHV-2), rangiferine herpesvirus 1 (RanHV-1) and elk herpesvirus 1 (ElkHV-1).…”
Section: Introductionmentioning
confidence: 99%